Once-Weekly Somapacitan as an Alternative Management of Growth Hormone Deficiency in Prepubertal Children: A Systematic Review and Meta-Analysis of Randomized Controlled Trial - Ghina Tsurayya; Cut Alifiya Nazhifah; Muhammad Rahmat Pirwanja; Putri Oktaviani Zulfa; Muhammad Raihan Ramadhan Tatroman; Fajar Fakri; Muhammad Iqhrammullah (Children, 2024)
Growth hormone treatment has effectively restored normal growth in children with growth hormone deficiency (GHD); however, it poses challenges in compliance with a daily growth hormone injection regimen, leading to low adherence and persistence rates. Once-weekly Somapacitan is a potential alternative for treating children with GHD. This study aimed to evaluate the efficacy, safety, and adherence of once-weekly subcutaneous Somapacitan compared to daily growth hormone injection in prepubertal children with GHD. A search for the published records was carried out on 17 October 2023 utilizing the searching feature available on PubMed, Embase, and Scopus. Primary study outcomes included (1) efficacy, measured by height velocity (HV), standard deviation score (SDs), height SDs, insulin-like growth factor-SDs (IGF-I SDs), and bone age vs. chronological age ratio (BA vs. CA); (2) safety, assessed through adverse events and injection site reactions; and (3) adherence, determined by the percentage of the sample completing treatments. Secondary outcomes evaluated disease burden scores, divided into three subgroup domains: emotional well-being, physical functional, and social well-being scores. We retrieved 6 studies that were eligible for the systematic review (417 versus 186 for intervention and control, respectively). Only 2 of the total included studies were eligible for pooled analysis (175 versus 82 for intervention and control, respectively). The efficacy profile of Somapacitan was similar to daily growth hormones, indicated by HV (mean difference (MD = 0.04; p = 0.96), HV SDs (MD = −0.71; p = 0.09), height SDs (MD = 0.11; p = 0.69), IGF-I SDs (MD = 0.06; p = 0.70), and CA vs. BA (MD = 0.67; p = 0.70)), demonstrated similar and non-inferior outcomes. Treatment adherence is 3 times higher in the Somapacitan group as compared to control (OR = 3.02; p = 0.03) with adherence rates reaching 95% and 88% for Somapacitan and Norditropin®, respectively. The disease burden measurement is similar in Somapacitan and daily growth hormones (MD = −0.62; p = 0.83), as indicated by the Growth Hormone Deficiency–Child Impact Measure. In almost all outcomes, the level of confidence is strong. The confidence level in the data is generally strong, but for CA vs. BA and the subgroup of severe adverse events with heterogeneity >50%, the confidence level is moderate. Although the efficacy and safety profiles of Somapacitan were found to be similar to those of daily growth hormones, a reduced frequency of once-weekly Somapacitan injections led to increased adherence. PROSPERO registration: CRD42023473209.